Identity and Erasure: Finding the Elusive Caribbean - Allahar, Anton (European Review of Latin American and Caribbean Studies, 2005)
– Caribbean Autobiography: cultural identity and self-representation, by Sandra Pouchet Paquet. Madison, WI: The University of Wisconsin Press, 2002. – Decolonising the Caribbean: Dutch policies in a comparative perspective, by Gert Oostindie and Inge Klinkers. Amsterdam: Amsterdam University Press, 2003. – Ah Come Back Home: Perspectives on the Trinidad and Tobago Carnival, edited by Ian I. Smart, and Kimani S. K. Nehusi. Washington: Original World Press, 2000.